rme1 Mutation of Saccharomyces cerevisiae: map position and bypass of mating type locus control of sporulation. - Rine, J (1981)
Sporulation in Saccharomyces cerevisiae normally occurs only in MATa/MAT alpha diploids. We show that mutations in RME1 bypassed the requirements for both a and alpha mating type information in sporulation and therefore allowed MATa/MATa and MAT alpha/MAT alpha diploids to sporulate. RME1 was located on chromosome VII, between LEU1 and ADE6.